Electromagnetic Vorticity in a Square‐Well Crystal System Described by a Supersymmetric Wave‐Equation. Issue 1 (18th November 2019) - Manzetti, Sergio; Trounev, Alexander
Abstract: Vortices occur under all electromagnetic phenomena in quantized systems, as well as macroscopic systems. In particular, vorticity in square‐wells is of great appeal to the scientific community, as it models electromagnetic fields and formation of condensates in crystal lattices. A supersymmetric wave‐equation (SWE) is devised to model vorticity in a square‐well system, and the numerical results of several states of vorticity are shown by increased energy of the system. It is shown that square‐well vorticity obeys specific symmetries when modeled with the SWE and generates non‐overlapping vortices of the same spin. Nucleation of vortices when subjected to increased angular velocity and formation of giant vortices is also shown. This is of importance to the modeling of magnetism in quantum systems, and the generation of new results to describe quantum vorticity. Abstract : The eigenvalues of a supersymmetric wave equation show that the equation can describe both microscale as macroscale phenomena, from quantum to cosmic systems. The equation is used to model vorticity in a square‐well system, and the numerical results of several states of vorticity are shown by increased energy of the system.